1960
DOI: 10.1002/pol.1960.1204414412
|View full text |Cite
|
Sign up to set email alerts
|

Nonterminated polymeric anions: The initiation of polymerization of certain polar monomers

Abstract: The lack of a termination reaction in the anionic polymerization in tetrahydrofuran of styrene,',* a-methyl~tyrene,~ i~o p r e n e ,~ and methyl meth-acrylate5 has been demonstrated, as has the utilization of certain of these polymeric anions as initiators of polymerization of a second monomer to form block copolymer~.~b~~~6 In this paper we report some extensions of this technique to the incorporation into such block copolymers of alkyl methacrylates, isopropyl acrylate, methacrylonitrile, and acrylonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The composition was determined by carbon and hydrogen analyses, and the density was measured at 20°C by the flotation method with aqueous solutions of calcium chloride. The number-average molecular weight (Mn) was determined by GPC with a Waters Model R-4 as based on a calibration curve of monodisperse polystyrenes (Waters Table I According to the method by Graham, et al, 14 the block copolymers, Z-1 and Z-2, were produced by the addition of CDA to living polystyrene anions initiated with n-butyllithium-tetrahydrofuran in toluene as solvent under highly reduced pressure mmHg) at room temperature. The obtained block copolymers were purified and dried by the same methods as used in the case of the random copolymers.…”
Section: Preparation Of Random Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition was determined by carbon and hydrogen analyses, and the density was measured at 20°C by the flotation method with aqueous solutions of calcium chloride. The number-average molecular weight (Mn) was determined by GPC with a Waters Model R-4 as based on a calibration curve of monodisperse polystyrenes (Waters Table I According to the method by Graham, et al, 14 the block copolymers, Z-1 and Z-2, were produced by the addition of CDA to living polystyrene anions initiated with n-butyllithium-tetrahydrofuran in toluene as solvent under highly reduced pressure mmHg) at room temperature. The obtained block copolymers were purified and dried by the same methods as used in the case of the random copolymers.…”
Section: Preparation Of Random Copolymersmentioning
confidence: 99%
“…A block copolymer presents a contrast to a random copolymer in the sequential distributions. Graham, et a!., 14 noted that isopropyl acrylate could give a AB-type block copolymer with living polystyrene anions initiated by nbutyllithium-tetrahydrofuran, but other acrylates such as ethyl and cyclohexyl acrylates had not polymerized well. In our laboratory, however, a AB-type block copolymer of cyclododecyl acrylate and styrene could be obtained according to the Graham's method.…”
mentioning
confidence: 99%
“…Anions of polystyrene (from butyllithium in THF) and of poly(MMA) (from 9-fluorenyllithium) have been shown to initiate the polymerization of alkyl methacrylates (hexyl, butyl), methacrylonitrile, isopropyl acrylate, and acrylonitrile. This authors (38) found that the poly (MMA) anion was unable to initiate the polymerization of styrene. 9-Fluorenyllithium, although sufficiently basic to initiate the polymerization of MMA, was also found to be unable to initiate the polymerization of styrene, and no styrene was found in copolymerizations initiated by this catalyst involving both monomers.…”
Section: «-Buli-et3aimentioning
confidence: 96%
“…In contrast, chain transfer is facile for acrylates due to the presence of an acidic proton at the carbonyl a-position (10,13,(33)(34)(35)(36). Again, only bulky monomers such as isopropyl and f-butyl acrylate (*BuA), may be polymerized anionically to high conversion with even moderate degrees of control.…”
Section: Side Reactionsmentioning
confidence: 99%